Community Empowerment through Optimization of Coconut Waste with Zero Waste Method : Pemberdayaan Masyarakat Melalui Optimalisasi Limbah Kelapa dengan Metode Zero Waste - Asfar, Andi Muhammad Irfan Taufan; Adiansyah, Romi; Nur, Syarif; Asfar, Andi Muhamad Iqbal Akbar; Nurannisa, Andi (Universitas Lancang Kuning, 2025)
This community service (PKM) aims to empower partners through zero waste methods in processing coconut waste into cocopeat and cocofiber products. The partner in this PKM is Poktan Wanua Cina, which is located in Tanete Village, Cina District. Activities include counseling, training, and mentoring. The results of the counseling showed an increase in partner knowledge and understanding, with an average score of 59.82. Counseling succeeded in increasing partners' awareness and motivation about the importance of coconut waste processing. Training showed an increase in partners' technical skills with an average increase of 59.55. Mentoring is intended to ensure that partners can apply the knowledge and skills that have been obtained. The mentoring results showed an average increase of 63.91. This PKM activity has proven effective in empowering partners with the resulting products having the potential to become village superior products.